THE INFLUENCE OF THE USE OF GEOGRAPHIC INFORMATION SYSTEM (GIS) APPLICATION AS A GEOGRAPHIC LEARNING MEDIA TO IMPROVE ENVIRONMENTAL KNOWLEDGE OF THE ELEVENTH GRADESTUDENTS OF SMA MUHAMMADIYAH 1 PALEMBANG - Ardiansyah, Molly; Disurya, Ramanata; Giyanto, Giyanto (Tadulako Social Science and Humaniora Journal, 2020)
Basically, a geographical information system is a system consisting of interrelated components (related) in achieving a goal, based on information (data, facts, conditions, phenomena) based on geographical conditions (regional, spatial, spatial) whose positioncan be checked in Earth's surface (geographical reference). The problem in this study waswhether the use of Geographic Information Systems (GIS) applicationas a medium of learning geography influenced the improvement of environmental knowledge of the eleventh gradestudents of SMAMuhammadiyah 1 Palembang. The purpose of this research wasto determine whether the use ofGeographic Information System (GIS) applicationas a Geography learning media affects the improvement of environmental knowledge of thestudents in the subject of disaster mitigation. This study utilizedquantitative descriptive methods using data collection techniques through test questions, and documentation. The sample collection technique used in this research wasrandom sampling. Data analysis techniques used wereHomogeneity Test and Hypothesis test, data presentation and drawing conclusions or data verification flow. The results of this study indicated that the use of Geographic Information Systems (GIS)application as a learning media for Geography increased the learning outcomes or knowledge about environment of class XI IPS 2 (Experiment) which was better with a value of 78.13 than XI IPS 1 (Control) with a value of 66.50.